2016
DOI: 10.1186/s12912-016-0177-z
|View full text |Cite
|
Sign up to set email alerts
|

Retaining early career registered nurses: a case study

Abstract: BackgroundA core objective of the Australian health system is to provide high quality, safe health care that meets the needs of all Australians. To achieve this, an adequate and effective workforce must support the delivery of care. With rapidly changing health care systems and consumer demographics, demand for care is increasing and retention of sufficient numbers of skilled staff is now a critical priority to meet current and future health care demands. Nurses are the largest cohort of professionals within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…This, coupled with increasing healthcare demand, provides an imperative for universities and industry to adequately prepare and retain those new to the nursing profession as a key priority. Evidence from recent years indicates that the rates of graduates who leave or intend to leave is increasing and costly (Booth, 2011;D'Ambra & Andrews, 2014;Flinkman & Salanterä, 2015;Hayes et al, 2012;Health Workforce Australia, 2012b;Laschinger, 2012;Laschinger, Finegan, & Wilk, 2009;North et al, 2013;Mills, Chamberlain-Salaun, Harrison, Yates, & O'Shea, 2016;Mills, Woods, Harrison, Chamberlain-Salaun, & Spencer, 2017;Trepanier, Early, Ulrich, & Cherry, 2012;Zimmerman & Ward-Smith, 2012). This evidence reinforces suggestions that graduates are not adequately prepared for practice and current healthcare demands.…”
Section: Introductionmentioning
confidence: 99%
“…This, coupled with increasing healthcare demand, provides an imperative for universities and industry to adequately prepare and retain those new to the nursing profession as a key priority. Evidence from recent years indicates that the rates of graduates who leave or intend to leave is increasing and costly (Booth, 2011;D'Ambra & Andrews, 2014;Flinkman & Salanterä, 2015;Hayes et al, 2012;Health Workforce Australia, 2012b;Laschinger, 2012;Laschinger, Finegan, & Wilk, 2009;North et al, 2013;Mills, Chamberlain-Salaun, Harrison, Yates, & O'Shea, 2016;Mills, Woods, Harrison, Chamberlain-Salaun, & Spencer, 2017;Trepanier, Early, Ulrich, & Cherry, 2012;Zimmerman & Ward-Smith, 2012). This evidence reinforces suggestions that graduates are not adequately prepared for practice and current healthcare demands.…”
Section: Introductionmentioning
confidence: 99%
“…The published research is largely from low‐income countries with a dearth of research from developed countries despite nurse migration resulting in major workforce planning challenges. Studies have identified the need for greater understanding of the factors that influence new graduates’ decisions to migrate, and the importance of examining novel ways of recruiting and retaining new graduates has been identified (Jones, Johnstone, & Duke, 2016; Mills, Chamberlain‐Salaun, Harrison, Yates, & O’Shea, 2016). This exploration requires in‐depth understanding of the factors influencing final‐year nursing/midwifery students’ intentions to migrate after registration.…”
Section: Introductionmentioning
confidence: 99%
“…New graduate health practitioners undergo a challenging period of adjustment that requires support 6 particularly in a rural and remote contexts 32,33 . Well‐structured support programs, with organisational commitment, have been shown to achieve successful outcomes in professional development and retention of early career health professionals 28,34‐37 . In this evaluation, the supervisor role was reported as an enabler to engagement in the RGP, managing workloads and achieving learning outcomes, while conversely, unstable staffing in the supervisor role was reported as a barrier.…”
Section: Discussionmentioning
confidence: 94%